Quality of life in cancer patients undergoing chemotherapy - Zielińska-Więczkowska, Halina; Betłakowski, Jacek (Contemporary Oncology/Współczesna Onkologia, 2010)
Background : Cancer is a serious problem in modern societies. The aim of the study was to estimate the influence of chemotherapy on quality of life in cancer patients. Material and methods : The study included 182 cancer patients of the Oncology Centre, Bydgoszcz, and was conducted between September 2008 and June 2009. To estimate the influence of chemotherapy on quality of life, the patients were divided into two groups: group A – 77 patients before the chemotherapy course and group B – 105 patients undergoing standard chemotherapy in hospital. Quality of life was assessed using EORTIC QLQ-C30 (3.0 version) for cancer patients. Results: Group B patients (undergoing chemotherapy) showed lower values in quality of life and health parameters and suffered from more symptoms (especially nausea) than group A patients who had not started their chemotherapy. However, group A patients also showed lowered values of quality of life parameters. The difference between the two examined groups was not statistically significant. Conclusions: Cancer and chemotherapy reduce quality of life. However, it is the diagnosis rather than the treatment that is responsible for lowering quality of life, as there are no statistically significant differences between the groups. Patients undergoing chemotherapy have the lowest scores in emotional functioning. The most troublesome symptoms include tiredness, sleep problems and pain.